The orexinergic neural pathway from the lateral hypothalamus to the nucleus accumbens and its regulation of palatable food intake. (April 2020) - Liu, Xiaoning; Gao, Shengli; Zhang, Nana; Jin, Tingting; Sun, Xiangrong; Luan, Xiao; Xu, Luo; Guo, Feifei
Abstract: Objective: To explore the orexinergic pathway from the lateral hypothalamus (LHA) to the nucleus accumbens (NAc) and its regulation on the palatable food intake. Methods: Fluorescent gold retrograde tracing combined with fluoro-immunohistochemical staining were used to observe the projection of orexinergic neurons from LHA to NAc. The orexin-A expression in LHA and c-Fos in NAc were studied after electrical stimulation of LHA. The firing rates of neurons were monitored by single-unit extracellular electric discharge recording and the palatable food intake were measured after orexin microinjection in NAc or electrical stimulation of LHA. Results: (1) Fluorescent gold retrograde tracing combined with fluoro-immunohistochemical staining showed some orexinergic neural projection from the LHA to the NAc shell. (2) Electrical stimulation of LHA significantly enhanced the expression of orexin-A in LHA and the expression of c-Fos in NAc ( P  < .05). (3) The results of single-unit extracellular discharge recording showed that the microinjection of orexin in NAc or electrical stimulation of LHA significantly increased the discharge activity of gastric distension responsive neurons in NAc, and the effect could be partly blocked by pretreatment of orexin-A receptor inhibitor SB334867 in NAc ( P  < .05). (4) Microinjection orexin-A in NAc or electrical stimulation of LHA significantly increased the palatable food intake in rats, and the effect also was partly inhibited by pretreatment of SB334867 in NAc ( P  < .05). Conclusion: There is an orexinergic pathway from LHA to NAc, which may have potential regulatory effects on food reward and obesity.